Effects of two different bleaching agents on surface roughness and microhardness of different novel nano-restorative materials - Bicer, Ceren Ozge; Oz, Fatma Dilsad; Attar, Nuray (European Journal of General Dentistry, 2017)
Objectives: The aim of this study was to evaluate the effects of 15% hydrogen peroxide (Illuminé Office) and 16% carbamide peroxide (VivaStyle) on the surface roughness and hardness of nano-restoratives. Materials and Methods: A total of 30 specimens of each material were fabricated using Clearfil Majesty Esthetic (Group1), Tetric EvoFlow (Group2) and Ketac N100 (Group3). Each group were divided into 3 subgroups and treated as follows: Group 1a, 2a, 3a was treated with Illuminé Office, Group 1b, 2b, 3b was treated with VivaStyle, Group 1c, 2c, 3c was stored in distilled water at 37°C for two weeks (control). Surface roughness and microhardness tests were performed. Results: There were no significant differences in terms of roughness and microhardness among Clearfil Majesty Esthetic and Tetric EvoFlow groups, seperately (P > 0.05). Illuminé Office increased the roughness and decreased the microhardness of Ketac N100 (P < 0.05). Conclusion: Bleaching may affect the roughness and microhardness of nano-restoratives depending on material and bleaching system.
Keywords: Bleaching; microhardness; nano restorative; surface roughness